Coverage of the situation of Western Armenians in Egyptian-Armenian press (1899-1904) - Myasnik Esoyan (Banber Arevelagitut'yan Instituti, 2023)
The developing relations of production caused a great revival in the economic life of Egypt starting with the second half of the 19th century. Armenians who migrated to Egypt took an active part in the development of the country's economic and cultural life. The revitalization of the economic and cultural life of Egypt has caused significant positive changes in the social and cultural life of Egyptian Armenians, where the Armenian periodical press has been doing a lasting job. The Egyptian-Armenian press has always been concerned about the situation in Western Armenia and Cilicia. In addition, Egyptian-Armenian periodicals have set themselves the task of keeping alive the hope of reviving the Motherland, uniting the Armenian immigrants settled in different countries all across the world around that idea.